Use of Heavy Water (D2O) in Developing Thermostable Recombinant p26 Protein Based Enzyme-Linked Immunosorbent Assay for Serodiagnosis of Equine Infectious Anemia Virus Infection - Harisankar Singha; Sachin K. Goyal; Praveen Malik; Raj K. Singh (The Scientific World Journal)
Thermostabilizing effect of heavy water (D2O) or deuterium oxide has been demonstrated previously on several enzymes and vaccines like oral poliovirus vaccine and influenza virus vaccine. In view of the above observations, effect of heavy water on in situ thermostabilization of recombinant p26 protein on enzyme-linked immunosorbent assay (ELISA) for serodiagnosis of equine infectious anemia virus (EIAV) infection was investigated in the present study. The carbonate-bicarbonate coating buffer was prepared in 60% and 80% D2O for coating the p26 protein in 96-well ELISA plate and thermal stability was examined at 4°C, 37°C, 42°C, and 45°C over a storage time from 2 weeks to 10 months. A set of positive serum (n=12) consisting of strong, medium, and weak titer strength (4 samples in each category) and negative serum (n=30) were assessed in ELISA during the study period. At each time point, ELISA results were compared with fresh plate to assess thermal protective effect of D2O. Gradual increase in the stabilizing effect of 80% D2O at elevated temperature (37°C < 42°C < 45°C) was observed. The 80% D2O provides the thermal protection to rp26 protein in ELISA plate up to 2 months of incubation at 45°C. The findings of the present study have the future implication of adopting cost effective strategies for generating more heat tolerable ELISA reagents with extended shelf life.